The Usage of Progesterone Hormone and Ultrasonography for Early Pregnancy Detection in Local Iraqi Ewes - Emad Abood, Ahmed; Muhammad Aboud, Qusay; Abdulrahman Ghazi, Maysam; Salah Hasan, Mustafa (The Indian Journal of Animal Reproduction, 2025)
The study was designed to evaluate and compare the reliability of several diagnostic methods for early pregnancy detec tion. Fifteen multiparous, non-pregnant local Iraqi ewes aged 2–4 years, along with four breeding rams, were used in this experiment. All animals were housed at the College of Veterinary Medicine, University of Fallujah, from October 2024 to March 2025. Estrus synchronization in the experimental ewes was performed using Medroxyprogesterone Acetate (MPA) intravaginal sponges combined with 500 IU of eCG, followed by natural mating with the four rams. Mating occurred at the onset of estrus and this time point was considered day 0. Whole blood samples were collected from the 15 ewes on day 0, and additional samples were obtained on days 14, 21, and 30 post-insemination (PI) for serum pro gesterone (P4) analysis. Early pregnancy was assessed using transrectal ultrasonography (TRU) with a 7.5 MHz probe. Serum samples were also used to measure P4 concentrations. Based on the findings, the detection Accuracy (Acc) of ULR was low in early pregnancy (days 14-21 PI) and improved along with pregnancy progression (30 PI). Progesterone levels were significantly raised in pregnant ewes compared to non-pregnant and control throughout the period. In days 14-21 PI, the P4 test method was significantly more effective than ULR in predicting pregnancy. By day 30 PI, the reli ability of all methods improved, the P4 assay demonstrated approximately similar efficiency to ULR. In conclusion, the P4 assay is a more reliable method for detecting pregnancy during the early stages (days 14–21 PI). From day 30 onward, ultrasonography becomes a superior approach due to its higher reliability, cost-effectiveness, and ability to determine both pregnancy status and embryo/fetal number.